Redistribution of ecological groups and life forms of plants of the Volga delta pastures under the influence of pasturage - T. V. Dymova (Юг России: экология, развитие)
Pasturage of animals is old and regular kind of anthropological influence to the Volga delta pastures. High level of pasture loading leads to degradation of the delta fodder grass, changing of plant and redistribution of ecological groups and life forms of plants. According to this fact the author offers the measures complex of preserving, restoring, and further increasing of biological variety of the Volga delta pastures.